Kecerdasan Buatan (AI) dalam Pendidikan: Potensi, Implementasi dan Implikasi Etis - Nuriah, Siti; Yustiana, Yusi Riksa; Fahriza, Irfan; Dartina, Vina (Universitas Mathla'ul Anwar Banten, 2025)
The presence of Artificial Intelligence (AI) in educational practice should improve mobility and learning outcomes and enhance students' learning skills. On the other hand, students see AI as a system that helps them accomplish practical learning tasks. This condition creates conflicts and dilemmas in the use of AI in learning. Studies on AI in education recommend metacognition as an important ability for students to utilize AI well. The research aims to find the formulation of metacognitive competencies needed by students in using AI as content in curriculum guidance. The research method used Systematic Literature Review with PRISMA model. The results of the literature review show that metacognitive studies in education and adolescent development refer to a longitudinal study conducted by Roger Azevedo. The potential, implementation and ethical implications are integrated in the Curriculum guidelines in improving metacognitive skills related to AI use are 1) self-regulation, 2) critical thinking, and 3) decision-making processes. Guidance activities that can be done in developing metacognition should be inquiry-oriented such as paired activities (brainstorming), self-assessment, experiential activities, and information selection.